Strategi Modelling The Way Dapat Meningkatkan Aktivitas dan Kemampuan dalam Melakukan Sholat Wajib pada Siswa Kelas 3 SDN 80/I Muara Bulian - Ponimin, Ponimin; Rumainah, Rumainah; Aisyah, Siti (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study aims to examine the effectiveness of the Modelling the Way strategy in improving the activity and ability of third-grade students at SDN 80/I Muara Bulian in performing obligatory prayers. This strategy focuses on teachers serving as role models in demonstrating discipline and the proper way of performing prayers, enabling students to observe and imitate the behaviors presented. The study employed a quantitative approach with a simple experimental design, involving a sample of 30 students divided into two groups: an experimental group that received the intervention through the application of this strategy and a control group that did not. Statistical analysis, including t-tests and ANOVA, revealed a significant increase in the experimental group compared to the control group. The regression coefficient for the Experimental variable was 0.163, with a t-value of 4.001 and a significance of 0.001, indicating a significant positive effect, while the coefficient for the Control variable was 0.411, with a t-value of 5.065 and a significance of 0.000, showing an even stronger influence. Additionally, the Kolmogorov-Smirnov normality test results indicated that the residuals from the regression model followed a normal distribution (p = 0.565), confirming that the normality assumption was met. No multicollinearity issues were found in the model, as Tolerance and VIF values were within acceptable limits. These findings demonstrate that the Modelling the Way strategy is an effective method for establishing the habit of prayer among students, with teachers serving as key role models in the learning process. Furthermore, the study highlights the importance of the family environment in reinforcing the habits developed at school. Students who received parental support showed faster improvements in their prayer activities. Overall, the study indicates that role modeling in prayer practices by teachers, supported by a conducive family environment, can significantly impact the development of religious character in students, particularly in cultivating the habit of performing obligatory prayers.